Term Structure, Inflation, and Economic Growth in Selected East Asian Countries - Elshareif, Elgilani Eltahir (2007)
The issue of term structure of interest rates has been a much-researched area in economics and finance in several developed economies for over a century. It is argued that the term spread between long and short rates contain useful information about future interest rates, inflation, and real economic activity which is of great importance to policy makers. This study attempts, first, to determine whether there is a time-varying risk premium in the short-term interest rate, and secondly, to provide an in-depth study on the term structure of interest rates and its impacts on the movements of short-term interest rates, inflation rates and real output in the five selected East Asian countries via an extended model of Expectation Hypothesis Theory of Term Structure. The five selected Asian countries are Japan, South Korea, Malaysia, Thailand and the Philippines. These objectives are achieved through the employment of the Generalized Method of Moment and Ordinary Least Square with Newey-West standard errors and Heteroskedasticity and autocorrelation consistent covariance correction. One interesting finding of this analysis is that there is a small risk premium in the short-term interest rates of Japan and Thailand, whereas there is none in those of Korea, Malaysia and the Philippines. This implies the stability of the short-term interest rates in the latter. In all the five cases, regardless of a timevarying risk premium in the interest rate, the term spreads of all these countries seem to contain useful information for predicting movements in the short-term interest rates. On the other hand, for the case of predicting the path of inflation rate, only three countries, namely, Japan, Korea and Malaysia, indicate a possible increase in future inflationary pressure. The two other countries, the Philippines and Thailand, did not benefit any useful information regarding the future inflation rates from term spreads, Similarly, the term spread also does not provide any relevant information on the real output of Malaysia, the Philippines and Thailand. However, it does provide relevant information for the case of Japan and Korea. The estimated results and findings of this study provide some very useful insight on the information contained in interest rate term spreads of the five countries. This useful information on interest rate, inflation and economic activity can benefit both the government and private sectors of the five countries in developing macroeconomic policies and gaining competitiveness in the global market.